Effect of 2, 6-xylidine (DMA) on secretion of biomarkers for inflammation and neurodevelopment by the placenta. (February 2022) - Arita, Yuko; Kirk, Michael; Gupta, Neha; Antony, Ronny; Park, Hyeon-Jeong; Stecker, Mark M.; Peltier, Morgan R.
Abstract: Cigarette smoke enhances placental inflammation and interferes with steroidogenesis. However, the chemicals in the smoke responsible for these biological activities are unclear. 2, 6 xylidine (also called 2, 6 Dimethylaniline, DMA) is a component of cigarette smoke that has carcinogenic properties but its effects on the placenta are unknown. Therefore, we hypothesized that DMA may interfere with placental steroidogenesis or enhance placental inflammation. Placental explant cultures were treated with 0–50, 000 nM DMA and concentrations of progesterone (P4 ), estradiol (E2 ), testosterone (T), IL-1β, TNF-α, IL-6, sgp130, HO-1, IL-10, 8-Isoprostane (8-IsoP), and BDNF in the conditioned medium were quantified. Since many environmental toxins enhance the proinflammatory host response to infection, we also performed experiments on placental cultures co-stimulated with 10 7 heat-killed E. coli . DMA alone significantly reduced P4 and T secretion but enhanced E2 secretion. The toxin also reduced placental secretion of IL-6, sgp130, and BDNF. For bacteria-stimulated cultures, DMA increased secretion of P4 and T, and proinflammatory cytokines (IL-1β, TNF-α) but had mixed effects on anti-inflammatory markers, increasing some (sgp130, IL-10) and reducing others (HO-1). However, DMA enhanced 8-IsoP levels by bacteria-stimulated placental cultures, suggesting that it increases oxidative stress by the tissues. These studies suggest that DMA affects secretion of biomarkers by the placenta and may promote inflammation. Further studies are needed to determine if these observed changes occur in vivo and the extent to which DMA exposure increases the risk of adverse pregnancy outcomes associated with smoking in pregnancy.